In Vivo evaluation of therapeutic potential of heart of date palm extract on lipid profile and thyroid hormones in normal male wistar rats - Trabzuni, Dina Mohammed (Progress in Nutrition, 2019)
Objective: Reports exist on the use of Phoenix dactylifera as hypolipidemic, hypoglycemic or antioxidant but broad search in the literature revealed absence of studies on the effect of heart of date palm (HDP) on lipid profiles and thyroid hormone and to the best of our knowledge this is the first research carried out to investigate the effect of heart of date palm extract (HDP) on lipid profiles and thyroid hormones. Method: Extract of heart of date palm was prepared by mixing 50 gram of finely powdered heart of palm flour with 400 ml distilled water. Sixty healthy male albino rats were divided into ten groups, comprising of six rats in each group. One group was kept as control while other 9 group was divided into three batches of Sukkari, Naboat Saif, Solleg. Each batch has three groups served with 1, 2 and 3 ml of HDP. After the completion of the experimental period (60 days) blood samples were collected from rat’s heart. Total Cholesterol, HDL Cholesterol, Triglycerides, Triodothyronine (T3), Thyroxin (T4) and TSH were determined for all groups. Result: HDP produced significant beneficial effect in the lipid profile of treated rats by significantly reducing total cholesterol and increasing HDL. LDLc, VLDLc and triglycerides also decreases with most of the treatment with some variations. Value of T3 and T4 significantly decreased, while the value of TSH significantly increased after treatment with HDP. Naboat Saif as compared to other two varieties (Sukkari and Solleg); exhibited better response towards lipid and thyroid hormones. Conclusion: This study shows that HDP supplementation may benefit management of lipid profile and thyroid hormones.